Structure Design of a New Type of Automatic Folding Stage - Sun Jianghong; Niu Xiaohui; Liu Xu (Jixie chuandong)
Aiming at the traditional stage is not easy to be moved or folded and some space is wasted,a new type of automatic folding stage is designed to make full use of the same space. The overall structure and the working principle of the stage are introduced,and the specific structure and principle of some mechanisms are described in detail,the statics analysis,kinematics analysis and dynamics analysis are carried out,the design basis is indicated. According to the structure and motion characteristic of the automatic folding stage,the control method of the mechanical and electrical is given to ensure the stage operation is safety and orderly. This design provide ideas for new folding mechanisms,as to as the optimization and innovation of the stage.